2001
DOI: 10.2460/javma.2001.219.346
|View full text |Cite
|
Sign up to set email alerts
|

Tissue disposition and depletion of penicillin G after oral administration with milk in unweaned dairy calves

Abstract: Liver had the highest concentration of penicillin G and was most likely to have violative residues. Feeding calves milk containing penicillin G has the potential to cause violative drug residues in tissues. It is recommended to observe an appropriate withdrawal time prior to slaughter if calves are fed milk from cows treated with penicillin G.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 19 publications
(10 reference statements)
2
9
0
Order By: Relevance
“…The penicillin concentration in the plasma at this same time is approximately 5 ng/mL. A similar 10:1 ratio has been reported in dairy calves by Musser et al. (2001).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The penicillin concentration in the plasma at this same time is approximately 5 ng/mL. A similar 10:1 ratio has been reported in dairy calves by Musser et al. (2001).…”
Section: Resultssupporting
confidence: 87%
“…The penicillin concentration in the plasma at this same time is approximately 5 ng/ mL. A similar 10:1 ratio has been reported in dairy calves by Musser et al (2001). This observation suggests that a concentration of less than 5 ng/mL in the plasma should correlate with a lower than tolerance concentration in the kidney.…”
Section: Analysis Resultssupporting
confidence: 87%
“…35 That practice has been associated with violative tissue drug residues in calves, 39 and FARAD has estimated slaughter WDIs for veal calves fed colostrum from cows treated with antimicrobials during the dry period (ie, the approx 45-to 60-day period prior to calving during which a dairy cow is not milked). 40 Results of other studies 41,42 likewise indicate that feeding calves milk replacer containing penicillin G or amoxicillin can result in violative tissue residues of those drugs. In 1988, calves fed milk or colostrum from medicated cows accounted for 39 of the 460 (8.5%) residue violations identified by the FDA.…”
Section: Waste Milk and Colostrummentioning
confidence: 99%
“…showed that it has to potential to be a good matrix for ante mortem sampling, but animal hydration status and consistency of status must be taken into account (Schneider et al, 2009). Musser et al (2001) showed that penicillin remains in higher concentrations in the urine for a greater length of time than in either tissues or serum in a study of oral penicillin G administration in dairy calves. That study determined urine would make a good ante mortem sample for residue testing (Musser et al, 2001).…”
Section: Alternative Residue Testing Matricesmentioning
confidence: 99%
“…Musser et al (2001) showed that penicillin remains in higher concentrations in the urine for a greater length of time than in either tissues or serum in a study of oral penicillin G administration in dairy calves. That study determined urine would make a good ante mortem sample for residue testing (Musser et al, 2001).…”
Section: Alternative Residue Testing Matricesmentioning
confidence: 99%